A comparison of the Butler-Volmer and asymmetric Marcus-Hush models of electrode kinetics at the channel electrode - Henstridge, M; Rees, N; Compton, R (2012)
We report a theoretical study of steady-state voltammetry at the channel electrode comparing the Butler-Volmer and Marcus-Hush (both symmetric and asymmetric) models of electrode kinetics. The latter model is shown, for small values of both reorganisation energy and standard rate constant, to exhibit a kinetically-limited steady-state current which is smaller than the mass-transport limiting current given by the Levich equation. However, the combination of parameters required to observe this kinetically-limited current is unlikely to occur in a 'real' system. We conclude that the Butler-Volmer model is sufficient to accurately model voltammetry under these conditions. © 2012 Elsevier B.V. All rights reserved.